2012
DOI: 10.1149/2.047301jes
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Redox Transition and Pseudocapacitance of Molybdenum/Surface Molybdenum Oxides

Abstract: Redox transitions and superior pseudocapacitance are two typical characteristics in the electrochemical behavior of metallic Mo (with surface Mo oxides) and bulk Mo oxides; both of which were attributed to the participation of H+/cations. The effects of different electrolyte anions (Cl−, SO42− and ClO4−) on redox transition and pseudocapacitance of thin-film ‘Mo/Mo oxides’ electrodes were assessed in this work through DC and AC electrochemical experiments. Voltammetric peak potentials and currents and potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(52 citation statements)
references
References 31 publications
5
47
0
Order By: Relevance
“…28,33 This result is consistent with the earlier report by Petitl et al, 41 where the authors showed that mass transfer limited slow electrodeposition of In on Mo cannot be detected with traditional CV. However, In deposited surface modifications of Mo were readily detected with optical second harmonic generation.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…28,33 This result is consistent with the earlier report by Petitl et al, 41 where the authors showed that mass transfer limited slow electrodeposition of In on Mo cannot be detected with traditional CV. However, In deposited surface modifications of Mo were readily detected with optical second harmonic generation.…”
Section: Resultssupporting
confidence: 92%
“…The decrease in C p after reaching a maximum can be associated with the hydrogen evolution process. 28 (b) Selenium CV recorded in Se(IV) electrolyte showed primarily two reduction peaks, C 1 and C 2 (Figures 2A-2C), where C 1 could be attributed to surface oxide's reduction 28 and C 2 to H 2 Se formation (Eq. 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first peak can be attributed to the characteristic redox transition of Mo oxides. 8,13 The second peak may be due to a subsequent Mo oxide's reduction. Both the peaks were accompanied with a frequency decrease indicating mass gain.…”
Section: Methodsmentioning
confidence: 99%
“…13 In this work, we wish to report our findings on the electrochemical multi-coloration of surface Mo oxide bronzes electrochemically derived from Mo in neutral aqueous solutions. To the best of our knowledge this is the first report on the fabrication of red, blue, and yellow colored bronzes on Mo in aqueous solution by an electrochemical strategy.…”
Section: -11mentioning
confidence: 99%